Rancang Bangun Generator Pulsa Gelombang Ultrasonik dan Implementasinya untuk Pengukuran Jarak Antara Dua Obyek - Syafrudin, Agus; Suryono, Suryono; Endro Suseno, Jatmiko (BERKALA FISIKA, 2008)
An instrument of pulse generator of ultrasonic wave and its implementation for distance measurement between two objects have been created through analysis using oscilloscope. This ultrasonic wave may be used in a distance measurement, material reflection analysis, and product’s depth. An ultrasonic oscillator is made with set of IC 555 as the setter of pulse amount and multi vibrator mono stabile set of IC 555 as the oscillator of ultrasonic frequency, pulse amplifier through transistor BD 139. An ultrasonic transducer using transducer 400ST/R160 and micro controller AT89S51 is used for time setter. In the amplifier set of ultrasonic receiver, Op-amp CA 3204 is used. AT89S51 is used for time setter that is made repeatedly in order that the bounce may be read on oscilloscope through P1.0. After conducting an experiment, the effective working area frequency in pulse generator of ultrasonic wave is obtained in the frequency of 38.23 kHz. In the experiment on the amount of effective pulse, the maximum reach effectively is 16 pulses. In the experiment on the distance between two objects, the writer finds out that an instrument linier grade is 0.81773 against standard measurement with R=0.99954 and SD=0.457. Meanwhile on the material reflectivity test, the writer may concludes that the bigger material mass, the bigger its reflectivity. Keywords: pulse generator of ultrasonic wave, transducer